2020
DOI: 10.1002/chem.202003989
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Tellurium Derivatives of Corannulene: Serendipitous Discovery of a One‐Dimensional Stereoregular Coordination Polymer Crystal Based on Te‐O Backbone and Side‐Chain Aromatic Array

Abstract: Chemistry-A European Journal Scheme1.Synthesis of selenium derivatives of corannulene. Scheme2.Synthesis of at ellurium derivative of corannulene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Another milestone was reported in 2012, featuring pentakis(pinacolatoboryl)corannulene 2 [7h] by regioselective iridium‐catalyzed borylation reaction. Various kinds of sym ‐penta‐substituted corannulene derivatives can be prepared from these materials, [7] including pentaaryl‐, [7b,i] pentaalkynyl‐, [7b,d,e] pentaoxy‐, [7b] pentafluoro‐, [7l] pentathio‐, [7a–c,j,k,n] pentaselenyl‐corannulenes [7m,n] . Yet, other kinds of quintuply substituted corannulenes such as pentaphosphinyl‐, pentaphosphoryl‐, and pentaamino‐corannulenes have not been explored.…”
Section: Methodsmentioning
confidence: 99%
“…Another milestone was reported in 2012, featuring pentakis(pinacolatoboryl)corannulene 2 [7h] by regioselective iridium‐catalyzed borylation reaction. Various kinds of sym ‐penta‐substituted corannulene derivatives can be prepared from these materials, [7] including pentaaryl‐, [7b,i] pentaalkynyl‐, [7b,d,e] pentaoxy‐, [7b] pentafluoro‐, [7l] pentathio‐, [7a–c,j,k,n] pentaselenyl‐corannulenes [7m,n] . Yet, other kinds of quintuply substituted corannulenes such as pentaphosphinyl‐, pentaphosphoryl‐, and pentaamino‐corannulenes have not been explored.…”
Section: Methodsmentioning
confidence: 99%
“…Encouraged by these studies, we planned the synthesis of selenoether analogues and their oxidation to selenones (36− 40) in an effort to further enhance the electron affinity of the corannulene nucleus (Figure 10). 41 We observed that while the synthesis of some of the selenoethers are feasible, these compounds become unstable once they are oxidized. Therefore, they are of little value as electron acceptors.…”
Section: Non-fullerene Electron Acceptorsmentioning
confidence: 99%
“…Our interest in corannulene chalcogenides (see Section 2.2.) motivated us to synthesize a tellurium derivative 41 which was observed to oxidize to 9 during either the reaction or the purification process (Scheme 5). An examination with X-ray crystallography revealed that the oxide 9 gave rise to linear polymer chains (10) in the solid state.…”
Section: Scheme 2 Different Synthetic Approaches To Access Corannulen...mentioning
confidence: 99%
“…Tellurium is the heaviest, non-radioactive member of the chalcogen family after oxygen, sulfur, and selenium. 127–131 The unique properties of tellurium compounds are becoming increasingly crucial in inorganic and organic chemistry and materials science. The use of tellurium to replace selenium or sulfur in conjugated polymers provides these materials with new properties, including high polarization and dielectric constant, red-shifted optical absorption, and strong intermolecular interactions.…”
Section: Four Branches Of Polymer Crystalsmentioning
confidence: 99%
“…Then, a similar work on a 1D coordination polymer crystal based on a Te–O backbone was published by Barat et al in 2020. 128 The tellurium derivative was still monomeric in solution, and the crystal corannulene side chains that produced linear polymer chains formed a line spontaneously. Similarly, the polymer backbone was also made of tellurium–oxygen bonds (Fig.…”
Section: Four Branches Of Polymer Crystalsmentioning
confidence: 99%